Geometrias não euclidianas: elíptica e hiperbólica no ensino médio - Dario, Douglas Francisco (2014)
This work aims to contribute in including teaching of Non-Euclidean Geometry in high school. For this, a bibliographic research was made about the appearance of such geometries and introduce content for teaching of Elliptical and Hyperbolic Geometries, addressing the main topics listed by Curriculum Guidelines of Paraná, comparing them with Euclidean Geometry. Clarify that where quoted elliptic geometry, we are really dealing with Surface Spherical Geometry, for that this work be compatible with the Curriculum Guidelines of the State of Paraná. Although there are some propositions and their proofs, in most part of the work there aren´t theoretical studies and statements with all rigors mathematics requires, we seek to show the main concepts and use a language that can be understood by any person who is willing to understand and after studying, teach these geometries in school. In November 2013, during the XVII Semana de Matemática and III Encontro de Ensino de Matemática Câmpus de Pato Branco – PR of UTFPR, a mini-course was applied with part of this content to some participants. At the end of the mini-course a questionnaire was applied inquiring the basic knowledge, the current teaching situation of these geometries and aim to identify the interest in this issue and the real possibility of inclusion in the classrooms, the results can be found in the following work.